2022
DOI: 10.1186/s40851-022-00187-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations from reversible to irreversible stages during coral metamorphosis

Abstract: For corals, metamorphosis from planktonic larvae to sedentary polyps is an important life event, as it determines the environment in which they live for a lifetime. Although previous studies on the reef-building coral Acropora have clarified a critical time point during metamorphosis when cells are committed to their fates, as defined by an inability to revert back to their previous states as swimming larvae (here referred to as the “point of no return”), the molecular mechanisms of this commitment to a fate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…AGRL2 and AGRG4 are members of the GPCR. Recently, Ishii et al . (2022) reported that the GPCR gene expression pattern changes drastically during coral metamorphosis, suggesting that the GPCR may regulate biological and developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…AGRL2 and AGRG4 are members of the GPCR. Recently, Ishii et al . (2022) reported that the GPCR gene expression pattern changes drastically during coral metamorphosis, suggesting that the GPCR may regulate biological and developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, we selected those that were annotated as "GPCR Family 1" (PF00001) by the Protein families (Pfam) database. These sequences were added to a subset of a previously published dataset containing bilaterian GPCRs ( 53 ), and cluster analysis was carried out with CLANS ( 54 ).…”
Section: Methodsmentioning
confidence: 99%